Measuring Student’s Entrepreneurship Profile By Using PEC Instrument (A Case Study In Politeknik Manufaktur Bandung) - Dede Sujana, Achmad Muhammad, Gamawan Ananto Subekti (International Conference on Industrial Revolution for Polytechnic Education, 2019)
Abstract. Entrepreneurship is a characteristic that can be observed in the actions of a person or institution. Entrepreneurship includes a range of behaviors, skills and traits that support the development of innovation and creativity. Someone who always works better and is different from others, so that person is an entrepreneur. This research is a preliminary research that aims to produce the profile of entrepreneurial competence of Polman students in Bandung. From the profile of entrepreneurial competence, students are expected to formulate patterns of entrepreneurship development in Polman Bandung. The research method used is descriptive method, with ex post facto research type and survey data collection method through questionnaire. The instrument used in this study was adapted from the Personal Entrepreneurial Competencies (PEC) developed by McClelland with McBer & Co. The results of the study were processed with descriptive analysis statistics. The conclusion of the study shows that the profile dimensions of entrepreneurial competence and the average total score of Personal Entrepreneurial Competencies (PEC) Polman Bandung students are categorized as “medium” criteria, which means that each individual has competence in entrepreneurship, although the level still needs to be improved.